2018
DOI: 10.3390/ijerph15102111
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Best Management Practices to Reduce Phosphorus Loading to a Highly Eutrophic Lake

Abstract: Reducing nonpoint source pollution is an ongoing challenge in watersheds throughout the world. Implementation of best management practices, both structural and nonstructural, is the usual response to this challenge, with the presumption that they are effective. However, monitoring of their efficacy is not a standard practice. In this study, we evaluate the effectiveness of two wetland restoration projects, designed to handle runoff during high flow events and serve as flow-through retention basins before retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Nutrient removal by BMPs may diminish when installed in nonoptimal locations, , as evidenced by tile-drained flows bypassing agricultural BMPs . Some studies suggest placing BMPs in critical source areas, which are areas with land uses that tend to generate pollutants and/or high hydrologic connectivity to sensitive receiving waters. Indeed, a study by Du et al in the Liu River Watershed in China found that implementing conservation tillage and installing vegetated filters in critical source areas successfully reduced TN and TP loads in a small agricultural watershed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nutrient removal by BMPs may diminish when installed in nonoptimal locations, , as evidenced by tile-drained flows bypassing agricultural BMPs . Some studies suggest placing BMPs in critical source areas, which are areas with land uses that tend to generate pollutants and/or high hydrologic connectivity to sensitive receiving waters. Indeed, a study by Du et al in the Liu River Watershed in China found that implementing conservation tillage and installing vegetated filters in critical source areas successfully reduced TN and TP loads in a small agricultural watershed.…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that several studies have also identified little relationship between inflow nutrient concentrations and outflow nutrient concentrations from structural BMPs. , The sensitivity of BMP performance to inflow volumes and pollutant loads indicates that appropriate sizing of the BMP is a key factor affecting BMP nutrient removal performance. Indeed, there are instances where BMP function at the watershed scale is not as intended due to under-sizing of the BMP. , For example, an undersized stormwater bioretention basin in North Carolina resulted in a 10% reduction in TP, compared to 44% in the correctly sized basins . Future research on the collective impacts of seasonal variations, storm intensity and size, and influence of concentrations on BMP performance is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These impacts motivate water resources and land use managers to employ fluvial sediment management strategies, but the implementation of these strategies can be difficult. Challenges related to effective management include identifying source conditions of impairments (Giri et al, 2012; Hanief & Laursen, 2019), siting best management practices (BMPs) in the watershed (Himanshu et al, 2019; Qiu et al, 2018; Steinman et al, 2018; Strauch et al, 2013), quantifying the effectiveness of existing BMPs (Bishop et al, 2005; Engebretsen et al, 2019), and evaluating new BMPs for future climate scenarios (Jeon et al, 2018). BMP selection also needs to be tailored to the physiographic properties of the system under consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Non-engineering means mainly include the development of environmental regulations, fertilizer and nutrient management systems, and integrated pest management techniques [7,8]. Although these methods have achieved positive outcomes, they have been limited by certain issues [10,11]. The most prominent challenge is that farmers lack the willingness to voluntarily participate in these practices [12].…”
Section: Introductionmentioning
confidence: 99%